1999
DOI: 10.1093/humrep/14.7.1869
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and birth resulting from transfer of a blastocyst observed to have one pronucleus at the time of examination for fertilization: Case report

Abstract: This case report describes a successful full-term pregnancy and birth after the transfer of a zona-free blastocyst derived from an oocyte observed at fertilization check as having only one distinct pronucleus (PN). The patient had previously undergone four in-vitro fertilization (IVF) cycles and three frozen embryo transfer cycles, with one pregnancy resulting. In this IVF cycle, 7/19 oocytes were fertilized exhibiting two distinct PN; however, all these oocyctes failed to develop in culture and had arrested o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Gras and Trounson suggested extended culture beyond the cleavage stage in an effort to assess the potential of these embryos to develop to the blastocyst stage as a better predictor of genetic normalcy (1). In the present report, our patient was 41 years old and had a markedly elevated FSH level.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Gras and Trounson suggested extended culture beyond the cleavage stage in an effort to assess the potential of these embryos to develop to the blastocyst stage as a better predictor of genetic normalcy (1). In the present report, our patient was 41 years old and had a markedly elevated FSH level.…”
Section: Discussionmentioning
confidence: 56%
“…Staessen and Van Steirteghem found that 48.7% of embryos developing from single pronucleated oocytes were diploid after IVF and 27.9% after ICSI (7). The potential of embryos derived from such oocytes to cause a normal pregnancy has been the subject of only three reports in the literature (1,6,8). The initial report by Staessen et al described two births out of 38 transfers of a single embryo resulting from a zygote with one pronucleus (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, cytogenetic analysis has revealed that a proportion of diploid embryos can develop from 1PN zygotes [1]. Healthy babies developing from such embryos have been reported [2]. On the other hand, 2PN zygotes are not necessarily euploid.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of 1PN zygotes are incapable of further development, a small number develop to the blastocyst stage. Moreover, they successfully progress to a live birth in cases where no other embryos exist of better quality [30][31][32] and despite the low pregnancy rate. Nevertheless, because of the uncertainty of their genetic normality, transferring such embryos is controversial among ART laboratories.…”
Section: Aberrant Behavior Of Female Pn (Fpn) During the Pronuclear Smentioning
confidence: 99%